Comunidades remanescentes dos quilombolas de Arvinha e Mormaça: processos educativos na manutenção e recuperação do território - Oliveira, Heron Lisboa de (Universidade do Vale do Rio dos Sinos, 2014)
The present thesis analyses the education process of two communities of remaining quilombolas – Arvinha and Mormaça – localizated on the countryside at the towns of Coxilha and Sertão, northeast of Rio Grande do Sul. Since 2004 the remaining communities have been acknowledged by Fundação Cultural Palmares. Arvinha and Mormaça are communities which fight for the maintenance and recovery of their geographic space that they actually are occupying, because they has the purpose of a process which includes autonomous work and freedom of subservience. The investigative process utilized the following methodologies: participant observation, individual and collective interviews and documentary research. I seek to understand the issues about territory and territoriality, especially the communities of the racial ethnic groups which are self recognized. These groups have been fighting since their origin for their space, because they have the feeling to belong to that place. This thesis shows the reasons why the communities have been setting up survival strategies in the last 160 years, which one we understand as educational strategies linked to teaching and learning, with the intention to avoid that their knowledge will be absolved by brazilian society. Those strategies are based in the relations between the group’s members, and it has established and made possible the cohesion at the group, enabling a primitive clustering of people, and after that it became a community. It is an education process which the communities have experienced for a long time and it’s very significant at the daily life, at the relationship with the housemates, the relatives, the neighborhood, and, the biggest group, the community. Therefore, it’s a process of teaching and learning non-schooled, which is linked with the personal history of people, with the relationship with one another, the friendship, the relationship of “compadrio”. Finally, this process was able (and still is able) to preserve their space and don’t recede in the fight to keep the enlargement and originality of their areas.
Keywords: Educação; Comunidade quilombola; Território; Territorialidade; Education; Quilombola community; Territory; Territoriality; ACCNPQ::Ciências Humanas::Educação